DESIGN AND DEVELOPMENT OF CHILDREN NUTRITION MONITORING APPLICATION WITH KARTU MENUJU SEHAT ON VILLAGE KARANGDUREN JEMBER COMMUNITY HEALTH CENTER - Maulana Arsandy, Noor Robby; Sagirani, Tri; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Puskesmas are Community Health Center located in indonesia. Puskesmas of Karangduren village on Jember regency is one of the health services responsible for building healthy scope in Karangduren village area. One way is to monitor the health of children from an early age. To help monitor the health of the child, each parent is given a mother's and children's health book. However, there are problems when the KIA book is missing, it can be a problem if the puskesmas officer to perform the examination of the data. Due to the overall recording of data still using the general ledger media, consequently to review the lost data will require a long time and can hamper the performance of puskesmas officers in making reports to be given to the health service. In solving the problem then the authors propose a solution that is by making an application system that can store data, can search data and can monitor the child's health periodically.With the results of this study produced an application that can help puskesmas staff to process data, search data and monitor the health of children. So it is more effective and efficient in helping the work of puskesmas officers